Disturbed vertical E×B plasma drifts in the equatorial F2 region at solar minimum deduced from observed NmF2 and hmF2 variations - A. V. Mikhailov; M. Förster; T. Y. Leschinskaya (Annales Geophysicae, 1996)
Ground-based ionosonde and magnetic-field observations on the equatorial station Huancayo, ESRO4 neutral-composition measurements, and theoretical model calculations were used to analyze disturbed E×B vertical plasma drift during the phase of solar minimum in 1973. Vertical drifts calculated for disturbed days do not show the systematic decrease often mentioned in publications, and demonstrate strong dependence on IMF-Bz changes. It is confirmed with the help of our drift calculations that Bz turnings to a northward direction result in a decrease (up to reversal) of normal Sq (eastward during daytime and westward at nighttime) in the zonal component of electric field. Southward Bz excursions enhance normal Ey both in daytime and nighttime hours. Model predictions of Ey\'s reaction to IMF-Bz changes are discussed.